More than a `speed gene`: ACTN3 R577X genotype, trainability, muscle damage, and the risk for injuries - Del Coso, J.; Hiam, D.; Houweling, P.; Pérez, L. M.; Eynon, N.; Lucía, A. (European Journal of Applied Physiology, 2019)
A common null polymorphism (rs1815739; R577X) in the gene that codes for a-actinin-3 (ACTN3) has been related to different aspects of exercise performance. Individuals who are homozygous for the X allele are unable to express the a-actinin-3 protein in the muscle as opposed to those with the RX or RR genotype. a-actinin-3 deficiency in the muscle does not result in any disease. However, the different ACTN3 genotypes can modify the functioning of skeletal muscle during exercise through structural, metabolic or signaling changes, as shown in both humans and in the mouse model. Specifically, the ACTN3 RR genotype might favor the ability to generate powerful and forceful muscle contractions. Leading to an overall advantage of the RR genotype for enhanced performance in some speed and power-oriented sports. In addition, RR genotype might also favor the ability to withstand exercise-induced muscle damage, while the beneficial influence of the XX genotype on aerobic exercise performance needs to be validated in human studies. More information is required to unveil the association of ACTN3 genotype with trainability and injury risk during acute or chronic exercise.